Multidimensionality and measurement invariance of the revised developmental work personality scale. Issue 2 (3rd April 2023) - Wu, Rongxiu; Chiu, Chungyi; Dueber, David; Park, Mirang; Lange, Dustin; Umucu, Emre; Strauser, David
Abstract: The current study examined the factor structure, measurement invariance, and construct validity of the 14-item Revised Developmental Work Personality Scale (RDWPS) using a sample of 603 college students in a Midwest university of the United States. Exploratory and confirmatory factor analysis results indicated that the 11-item RDWPS resulted in a better fit of the measurement model. Partial measurement invariance was also detected between gender groups. In addition, it was weakly to moderately correlated with the Utrecht Work Engagement Scale-Student (UWES-S), self-reported effort, and GPA among college students. Lastly, it was found that males scored lower than females in all three subscales of the RDWPS in comparison to the latent means of the gender groups.